Antioxidant Therapy Restores Hepatic Metabolic Enzymes Altered by Exposure to Microcystin-LR in a Murine Model of Non-Alcoholic Fatty Liver Disease - Hunyadi, Jonathan (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.